Effect of water pressure and temperature on spherical float of level sensing auto drain valve. (2022) - Sundararaj, S.; Krishnakumar, P.; Anirudh, V.R.; Shikhar, L. Chetan; Surendhar, G.; Vijay, V.
Abstract: A float detects the level of a liquid in a tank or a container. It floats on top of the liquid surface and acts as a mechanical switch when the water moves up or down in the auto drain valve tank. The auto drain valve removes the water in the compressed air circuit The spherical float used in the auto drain valve is prone to the realization of a dent and the float joint fails due to the high pressure of air in the compressed air circuit. In this paper, the spherical float was analysed numerically to select the suitable stainless steel materials out of SS 302, SS 305, SS 312, SS 316 to withstand the high-pressure force and temperature of the air in the drain valve. The applied pressure was varied from 0.7 to 2.0 MPa and the temperature from 2 °C to 80 °C based on the drain valve application. The structural analysis results obtained were the total deformation, the equivalent stress, and the pressure at the joints of the float. Equations were obtained to get the relationships between applied pressure and temperature with equivalent stress and total deformation. The results indicate that both equivalent stress and total deformation varies linearly with pressure. With respect to temperature, equivalent stress varies linearly and total deformation varies in polynomial relation. The minimum and maximum values of total deformation obtained were 0 to 0.0132 mm, equivalent stress were 37.11 to 75.40 MPa and the average joint pressure was 12.43 to 76.56 MPa. The results show that SS 314 grade could be chosen for fabrication of spherical float in drain valve application.